TYPE AND ABUNDANCE OF PLANKTONIC DIATOMS IN RANGSANG BARAT WATERSDISTRICT MERANTI ISLAND RIAU PROVINCE - Mery Mery; Joko Samiaji; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Planktonic diatoms are plant-based microorganisms that live floating in the  water column, relatively lacking in motion and their presence is influenced by water quality and able to photosynthesize. This research was carried out in May 2018 in the waters of Rangsang Barat Meranti Islands Regency, Riau Province. This study aims to find out the type and abundance of planktonic diatomsin the waters of Rangsang Barat.The method used in this study was the survey method. Planktonic diatom sampling was using plankton net No. 25. The results of this study showed that the type and abundance of planktonic diatoms in Rangsang Barat waters at each station was different. The type most often type found at each station was the species Coscinodiscus sp.and Thalassiosira sp.The most rarely found species wereThalassionema sp. and Synedra sp. The highest abundance of planktonic diatoms was found at station II, in which reaches at 261.57 ind / l while the lowest was at station III with the value 48.61 ind / l. Based on the results of thetest One-Way, the  Anovaabundance of planktonic diatoms showed a significance value of> 0.05 i. e. 0.016, indicating the abundance of planktonic diatoms was significantly different. Keywords: Diatoms, Type, Abundance, Rangsang Barat Waters